2021
DOI: 10.1016/j.injury.2021.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intramedullary nailing and minimally invasive plate osteosynthesis for tibial shaft fractures

Abstract: Introduction: Intramedullary nailing (IMN) is currently considered the gold standard in the surgical treatment of tibial shaft fractures in adult patients. In this case-control comparative study, we aimed to compare the efficacy of minimally invasive plate osteosynthesis (MIPO) and IMN in treating tibial shaft fractures. Materials and methods:The clinical and radiological outcomes, such as a modified trauma scale, operation time, fracture healing, rate of re-operation, and complications such as malunion, nonun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The excellentgood rate of Johner-Wruhs scores was 100% that meant the limb function recovered satisfactorily. Besides, RBI decreased the VAS scores compared with previous studies and the control group at postoperative 2 weeks [17][18][19][20]. There was no venous thrombosis of lower limbs and postoperative complication occurred in any of the patients in RBI group so we thought that RBI might be safety to patients, however, this conclusion was needed many large sample-size randomized controlled trials to prove.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The excellentgood rate of Johner-Wruhs scores was 100% that meant the limb function recovered satisfactorily. Besides, RBI decreased the VAS scores compared with previous studies and the control group at postoperative 2 weeks [17][18][19][20]. There was no venous thrombosis of lower limbs and postoperative complication occurred in any of the patients in RBI group so we thought that RBI might be safety to patients, however, this conclusion was needed many large sample-size randomized controlled trials to prove.…”
Section: Discussionmentioning
confidence: 66%
“…The nonunion rate of tibia shaft fracture is about 14% that is much higher than the average nonunion rate of long-bone fracture [1][2][3]. As for reducing disruption of local blood supply, intramedullary nails have been wildly used in clinic at present [17][18][19]. Despite strict adherence to the guidelines, the healing time and nonunion rate of tibial shaft fractures are not decreased significantly [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, disunion and excessive pain in the knee region is observed in the case of nailing. The nailing treatment is only suitable for the fractures in the proximal region but beyond this line, this nailing method is more complicated [17][18][19] . The function of the ankle was assessed by the criteria of Merchant and Dietz.…”
Section: Discussionmentioning
confidence: 99%
“…13 Reamed IMN has become the mainstay of treatment for most adult tibial shaft fractures due to minimal soft tissue dissection, good bone union rate, and early return to daily living. 14 Cast immobilization is appropriate for low-energy tibial fractures with minimal soft tissue dissection; however, fractures with higher energy mechanisms involving more osseous and soft tissue disruption make closed reduction difficult to obtain and maintain. 13,15 In a study of 201 tibial shaft fracture cases, Puno et al reported IMN resulted in lower complication rates with one nonunion (1.7%), two infections (3.3%), and no malunions in 60 patients compared to closed reduction and casting, which resulted in 14 delayed unions or nonunions (9.9%), two infections (1.4%), and six malunions (4.3%) in 141 patients.…”
Section: Introductionmentioning
confidence: 99%